Impact of the COVID-19 Pandemic on Chronic Inflammatory Dermatoses: Mixed Messages Regarding the Dermatologist's Point of View and the Patient's Concerns - Anne-Claire Fougerousse; François Maccari; Ziad Reguiai; Edouard Begon; Valérie Pallure; Charles Taïeb; Céline Girard; Laure Mery-Bossard (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)